High school campus design elements for outdoor-based education amenities - Butler, Ninah (Kansas State University, 2013)
The research conducted in this thesis explores the relationship between high school campus planning and the potential for high school sites to be used as outdoor classrooms. A review of the design of school buildings and the educational pedagogy that has influenced campus planning and design is presented before exploring current design practices. Precedent studies are offered as examples of exemplary design strategies for multi-use campuses. This leads to the question, “What variables allow future outdoor based education opportunities to be anticipated by site designers of high school campuses?” Four units of analysis and their relationship with site planning will be addressed in this research: environmental factors, space requirements, building proximity, and activity type. A case study based on these units of analysis is used in a multiple case study investigation of three school campuses in the Wichita, Kansas area: Goddard High School, Eisenhower High School, and Maize High School. The methodologies of organization, implementation and analysis of the variables are presented. The patterns found from the multiple case study and the variables developed in response to these findings are offered and discussed. Finally design alternatives for the three case study sites and future research opportunities are provided.
Keywords: Site planning and design; Sustainability; Education; High school campuses; Outdoor-based educationLandscape architecture; Education, General (0515); Landscape Architecture (0390)